Constructs of project programme management supporting open innovation at the strategic level of the organisation - Matheusz Trzeciak; Tomasz P. Kopec (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
The main aim of the article is to fill the gap concerning the recognition of constructs of programme management supporting open innovations. Current knowledge on this subject is mainly limited to identifying success factors of open innovation and programme management. In the current literature, there are few publications indicating the use of the programme as a tool supporting innovation. In order to fill the identified knowledge gap, common factors of programme success and open innovations were compared and assessed successively. A quantitative study was conducted on an international group of experts, including 578 experts in programme management. As a result of applying cluster analysis and operationalising the obtained results, four programme constructs supporting open innovations were dimensioned, such as cooperation with the environment, transfer of knowledge and technology, organisational maturity, and ensuring and maintaining implementation capacity. Moreover, the discussion and the research revealed that the impact and scope of the structured approach to programme management not only allow for the implementation of the assumed outcomes and benefits at the strategic level, but also influence the shaping and adjustment of the whole organisation.
Keywords: 650; support for innovation; programme management; management of knowledge; projectmanagement